Surface tensions surgery, bodily boundaries, and the social self - Manderson, Lenore (Left Coast Press, 2011)
"Surface Tensions is an expansive, yet intimate study of how people remake themselves after catastrophic bodily change--the loss of limbs, the loss of function, the loss or replacement of organs. Against a sweeping cultural backdrop of art, popular culture, and the history of science and medicine, Manderson uses narrative epistemology based on in-depth interviews with over 300 individuals to show how they re-establish the coherence of their bodies, identities, and biographies. In addition to offering important new insights into the care, rehabilitation, and rehabituation of post-trauma patients, Manderson's work challenges conventional ideas about the nature of embodiment and is an important contribution to medical anthropology, disability studies, and cultural studies"--